The politics of Jean-François Lyotard : justice and political theory - Rojek, Chris; Turner, Bryan S. (Bryan Stanley), 1945- (Taylor & Francis, 1998)
Here leading experts tackle questions about the writings on justice and politics of diference, on feminism, youth and judaism by Jean-Francois Lyotard who is still considered to be the father of postmodernism.